IMPLEMENTATION OF PROJECT-BASED LEARNING (PjBL) MODEL IN DEVELOPING SKILLS AND CREATIVITY OF STUDENTS OF SMPN 2 LUBUK ALUNG IN ISLAMIC RELIGIOUS EDUCATION AND MORAL EDUCATION SUBJECTS - Sanur, Rahmayuli; Taftazani, Taftazani (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2025)
This study aims to describe the implementation of the Project Based Learning (PjBL) model in developing the skills and creativity of students at SMPN 2 Lubuk Alung in Islamic Religious Education. The method used was Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages with 32 students as research subjects. Data were collected through observation, documentation, and project assessment, then analyzed descriptively and qualitatively using percentage calculations. The results showed an increase in students' skills and creativity in each cycle. In the pre-cycle, the average skills and creativity of students were still low, at 39.4%. After implementing PjBL in cycle I, there was an increase to 63.3%, although there were still weaknesses in the aspect of creativity. In cycle II, the results increased significantly to an average of 84.4%, which means that almost all students were active, creative, able to work together, and had a high interest in participating in PAI learning. Thus, the application of Project Based Learning proved to be effective in improving students' skills and creativity and can be used as an alternative learning model that is fun, meaningful, and relevant to the demands of 21st-century education